PENGARUH PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 3 KEC. PANGKALAN KOTO BARU - Maharani, Hijri (Jurnal Edukasi dan Penelitian Matematika, 2024)
This experimental quantitative research analyses the effect of Creative Problem Solving model on the mathematical problem solving ability of students in class VIII SMPN 3 Kec. Pangkalan Koto Baru on students' mathematical problem solving ability. The design used was Posttest-Only Control. Experimental and control class students from SMPN 3 Kec. Pangkalan Koto Baru grade VIII in the 2023/2024 school year participated in this study. The sample selection was done by simple randomisation. Quiz and final test to collect data. Two-sample t-test for normality, homogeneity, and hypothesis testing were conducted. The final test results rejected H0 with a P-value of 0.006 and an actual level of 5%. H0 was rejected, therefore the experimental class learners answered the maths questions better than the control class learners. Thus, the Creative Problem Solving learning paradigm improves the mathematics problem-solving ability of grade VIII students at SMPN 3 Kec. Pangkalan Koto Baru.Keywords: Model CPS, Mathematical Problem Solving Skills, Direct Learning